Overeducation in Arab Labour Markets; Different Measures, Different Outcomes - Alattas, Halah (European Journal of Sustainable Development, 2023)
Since the introduction of the topic of overeducation, there has been a methodological debate on the most effective measurement tool. This debate has concluded that there is no single most appropriate method to measure overeducation, which depends entirely on data availability. By using the Integrated Labour Market Panel Survey (ILMPS) for Egypt (1998-2018), Jordan (2010-2016) and Tunisia (2014), this paper contributes to the existing literature on overeducation by measuring it across a sample of Arab countries using different methods as specified in the literature. The results reveal that the incidence of overeducation significantly varies across the measures. The subjective WA approach yielded the highest incidence of overeducation among the measures, whereas JA approach produced the lowest incidence. The RM approach, however, fell in a middle between the two other approaches and captured the region’s political conflict and social unrest. Moreover, the Spearman rank correlation between the measurements was relatively low, indicating short overlaps among workers categorized as overeducated across measures. Keywords: Overeducation, Arab countries, Workers’ self-Assessment, Job analyst, Realized Matches.